Pengaruh Kompetensi Profesional Guru Sd Terhadap Prestasi Belajar Siswa - Pontoh, Rati Anggraini; Chintya, Julien (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to determine the effect of elementary school teachers' professional competence on student achievement. Using a quantitative approach with a correlational method, the study was conducted with teachers and fifth- and sixth-grade students at several public elementary schools selected purposively. Data on teacher professional competence were obtained through a questionnaire based on indicators from the Minister of National Education Regulation No. 16 of 2007, while student achievement was measured from report card scores in Mathematics, Indonesian, and Science. Data were analyzed using Pearson correlation and simple linear regression. The results showed a positive and significant relationship between teacher professional competence and student achievement (r = 0.628; p < 0.05), with a contribution of 39.4% to the variation in learning achievement. These findings confirm that teachers with good mastery of material, curriculum understanding, and learning strategies can significantly improve student academic achievement. The study recommends strengthening ongoing teacher professional development programs to improve the quality of elementary education.